ANALISIS STRATEGI DAMPAK AKIBAT KENAIKAN HARGA KEDELAI TERHADAP LABA USAHA TEMPE - Amelia, Ocdy; Syaula, Maya; Sulardi, Sulardi; Rahmadani, Adinda Tantri (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
This study aims to determine the increase in the income of tempe producers, and the impact on regional and village productivity development. All populations that were used as samples were 5 samples. The analytical method used is descriptive and SWOT matrix. The success of increasing the income of tempe craftsmen can be realized if it is supported by the availability of good soybeans, the availability of tools and machines, as well as loan capital to the craftsmen, where this research plays an active role in running and increasing the business income of tempe producers. From the results of visits and interviews, it was obtained that the average business income of tempe craftsmen in the study area was IDR 8,171,500.-/month. This shows that the business activities of tempe craftsmen have sufficient income to create the welfare of their families. The right SWOT strategy for tempe producers in Klambir Lima Village in developing their business and increasing their income is an Aggressive Strategy based on the SO strategy. The quality factor of the Tempe is a factor that can be utilized by the Craftsmen in Klambir Lima Village to increase the selling price. So that the income received by the craftsmen's businesses will also increase and be sufficient to provide for the welfare of their families.